Trends in the disease burden of thyroid cancer among adolescents and young adults: A comparative study of China and global estimates (1990–2021) - Jiahui Qian; Shuo Qi; Rui Hu; Miao Zhang; Zhi Chen; Zhiguo Ding (PLoS ONE, 2025)
Objective This study aimed to assess temporal trends, epidemiological features, and sex differences in the thyroid cancer burden among adolescents and young adults, globally and in China, from 1990 to 2021, using the Global Burden of Disease 2021 data. We projected China’s future burden through 2041, to support precision prevention strategies. Methods Data on the incidence, prevalence, mortality, and disability-adjusted life years of thyroid cancer in AYAs were extracted from the Global Burden of Disease 2021 database. Age-standardized rates and estimated annual percentage changes were calculated. Joinpoint regression was used to detect shifts in trends. An age-period-cohort model was used to quantify the effects of age, period, and birth cohort on the incidence. Decomposition analysis was used to evaluate the contributions of population growth, aging, and epidemiological changes. A Bayesian age-period-cohor model projected future trends for China. Furthermore, we conducted a stratified analysis by sex to investigate the heterogeneity in the evolution of disease burden between the Chinese and global populations. Results Between 1990 and 2021, China experienced a rapid increase in the incidence and prevalence of thyroid cancer among adolescents and young adults; the age-standardized incidence rate increased by 152.6%, far exceeding the global average. Mortality and disability-adjusted life years declined, forming a pattern of high incidence, low mortality, and moderate disability. This increase was primarily driven by epidemiological transitions. In terms of sex differences, Males exhibited a sharper increase in both incidence and disability-adjusted life years than females, indicating growing sex-based disparities. Notably, the burden in China began increasing earlier and more rapidly than global trends, particularly in males, whose incidence continued to increase even as global rates stabilized. Age-period-cohort model analysis further revealed that, among the adolescent and young adult population in China, the incidence of thyroid cancer increased significantly with advancing age, the incidence risk potentially increased after 2010, and more recent birth cohorts born after 1980 also exhibited an upward risk trend. However, despite these patterns, neither the period nor cohort effect reached statistical significance. Finally, Bayesian age-period-cohort projections suggested that the incidence and prevalence will continue to increase over the next 20 years, while mortality will remain stable, and disability-adjusted life years will decline slightly. Conclusions Over the past three decades, the burden of thyroid cancer among adolescents and young adults in China has increased at a substantially accelerated rate compared to global trends, with a pronounced widening of the sex gap in disease burden. While Chinese female patients have continued to show improvements in prognosis and relative burden measures, male patients have experienced a marked rise in both incidence and disability-adjusted life years, accompanied by a consistent decline in prognostic outcomes. These findings underscore the need for sex-specific strategies: for males, prioritizing the identification and mitigation of modifiable risk factors to curb the rising burden and improve prognosis; for females, consolidating effective diagnostic and therapeutic practices while minimizing overdiagnosis. Gender-sensitive approaches, aligned with precision prevention, may help address the growing burden.